2017
DOI: 10.1007/s10549-017-4124-9
|View full text |Cite
|
Sign up to set email alerts
|

Oncoplastic surgery with omental flap reconstruction: a study of 200 cases

Abstract: The LHOF has minimal donor-site morbidity and deformity, and oncological safety is promising. There is a limit to the adaptable volume, but the LHOF is an attractive option in partial breast reconstruction after BCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 18 publications
0
40
1
Order By: Relevance
“…Initially, laparotomy was almost the only technique used. Successively, laparoscopy was more often performed for breast reconstruction in patients with early-stage breast cancer [7][8][9] and also for additional coverage of breast implants [10]. Interestingly, Claro et al reported that flap necrosis is the most frequent complication (31.87%), with the second most common complication being breast infection (19.05%), followed by abdominal wall hernia (16.12%) and bowel obstruction or ileus (9.16%).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, laparotomy was almost the only technique used. Successively, laparoscopy was more often performed for breast reconstruction in patients with early-stage breast cancer [7][8][9] and also for additional coverage of breast implants [10]. Interestingly, Claro et al reported that flap necrosis is the most frequent complication (31.87%), with the second most common complication being breast infection (19.05%), followed by abdominal wall hernia (16.12%) and bowel obstruction or ileus (9.16%).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have found that omental flap procedures are limited by possible volume insufficiency during reconstruction, which is difficult to predict preoperatively. [1][2][3]9,10 In this study, we were able to harvest as much omental tissue by meticulously dissecting the fused omentum around the hepatic flexure or the root of the right gastroepiploic pedicle and isolating the infrapyloric vessels as we would have had we used the same method employed in pylorus-preserving gastrectomy. 11,12 In conclusion, ICG-enhanced NIR imaging is a feasible and useful tool in terms of vascular perfusion for laparoscopically harvesting an omental flap in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…When immediate breast reconstruction using omental flaps was initially introduced, it was not actively performed because it required a laparotomy that left a large abdominal scar. However, recent advances in minimally invasive surgery have enabled surgeons to obtain an omental flap laparoscopically with less donor‐site deformity . Successful breast reconstruction using autologous tissue depends on flap viability.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the recent decades, the surgical management of breast cancer has steadily evolved from radical surgery to breast conservation. As a result, oncoplastic surgical techniques have emerged and are expanding dramatically . Oncoplastic surgery combines oncologic resection with immediate breast reconstruction using techniques derived from plastic surgery.…”
Section: Discussionmentioning
confidence: 99%